Pemberdayaan Masyarakat Melalui Penanaman Sayuran Hidroponik Sebagai Upaya Pencegahan Stunting - Sholikha, Miftakhus; Izza, Rohmatul; Putri Ulul Azmi, Mei; Mahmudifa, Ayu; Setyariningsih, Eny (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Stunting remains a chronic nutritional problem in Indonesia, including in urban areas such as Mojokerto City. Low consumption of nutritious vegetables due to limited land and poor soil quality is one of the contributing factors. This community service activity aims to empower the Asuhan Mandiri Tanaman Obat Keluarga (Asmantoga) Sriwedari group through training in hydroponic vegetable cultivation using the wick system as an effort to provide healthy food for stunting prevention. The implementation methods were designed using the Mission Model Canvas (MMC) framework, including an initial survey, material development, hydroponic technique training, practical planting guidance, and evaluation. The results of the activity showed an increase in participants' knowledge and skills in growing hydroponic vegetables. The hydroponic vegetables cultivated (water spinach, spinach, mustard greens, and lettuce) have nutritional content, particularly calcium, which plays an important role in preventing stunting. Community enthusiasm and active participation were key factors in the program's success. Thus, the application of hydroponics is not only a solution to land constraints but also a sustainable community empowerment strategy to enhance household-level nutritious food security.